Obtaining high-resolution synthetic soil imagery for topsoil mapping. Issue 2 (1st February 2022) - Ruiz, Luis Fernando Chimelo; Dematte, José Alexandre Melo; Safanelli, José Lucas; Rizzo, Rodnei; Silvero, Nelida E. Q.; Rosin, Nícolas Augusto; Campos, Lucas Rabelo
ABSTRACT: Detailed soil maps contribute to the understanding of agricultural and food value chains. PlanetScope satellite constellations have high spatial and temporal resolution and could be used to develop Synthetic Soil Image (SYSI) at specific dates of field crops calendar. This work aimed to derive a SYSI from PlanetScope time series and estimate soil clay content, an important attribute related to several soil functions. The normalization process was applied to make the radiometries of the different Doves' images compatible and, subsequently, land cover classification was performed to select the bare soil class, obtaining the SYSI-Planet. The clay content was predicted for 2337 topsoil samples using the SYSI-Planet and Random Forest algorithm. The normalization of PlanetScope images were based on reference images, which mitigated the radiometric differences from acquisition dates and different radiometric calibrations. SYSI-Planet resulted in an excellent clay content prediction, resulting in a coefficient of determination ( R 2 ) equal to 0.93 and Root-Mean-Square Error (RMSE) equal to 70.90. The predicted clay mapped revealed spatial patterns with a high spatial resolution ( 3 m), which can enhance precise agricultural management.